Advanced biomaterials fundamentals, processing, and applications (John Wiley & Sons, 2009)
Advanced Biomaterials: Fundamentals, Processing, and Applications reviews the latest biomaterials discoveries, enabling readers to take full advantage of the most recent findings in order to advance the biomaterials research and development. Reflecting the nature of biomaterials research, the book covers a broad range of disciplines, including such emerging topics as nanobiomaterials, interface tissue engineering, the latest manufacturing techniques, and new polymeric materials.